Գարեգին Ա. Քեսաբցի Կաթողիկոսի քարոզխօսութեան լեզուական առանձնայատկութիւնները - Մեսրոպեան, Հայկանուշ (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В статье мы представили лингвистические особенности проповеди Като- ликоса Гарегина Кесабци, являющемся классическим примером проповедника. Проповеди Патриарха отличаются убедительностью, христианской верой, патриотическими идеями, богатой лексикой, характерной для риторического стиля, образным языком, разнообразными выразительными средствами, характерными для художественной речи. Язык произведений Его Святейшества — литературный западноармянский. В последние годы жизни восточно- армянская среда наложила свой отпечаток на речь Гарегина Первого. Богатый язык его проповедей и описательная лексика соединяют восточноармянский и западноармянский современные литературные языки, способствуя взаимообогащению двух ветвей литературного языка. Мы рассмотрели особенности литературных слов, авторских неологизмов, архаизмов, поэтических и редко используемых слов, терминов, заимствований, а также средства изображений, характерные для художественной речи: наречий и сравнений, метафор, олицетворений и т. д. In the article, we presented the linguistic features of the sermons of Catholicos Karekin of Kessab, who is a classic example of a preacher. The Catholicos’ sermons are characterized by persuasiveness, Christian faith, patriotic ideas, a rich vocabulary characteristic of the rhetorical style, figurative language, and various expressive means characteristic of artistic speech. The language of the works of Karekin I is literary Western Armenian. In the last years of his life, the Eastern Armenian milieu left its mark on the speech of His Holiness. The rich language of his sermons and the descriptive vocabulary combine the modern literary Eastern Armenian and Western Armenian, contributing to the mutual enrichment of the two branches of the literary language. We have considered the features of literary words, authorial neologisms, archaisms, poetic and rarely used words, terms, borrowings, as well as the means of imagery characteristic of artistic speech: adverbs and comparisons, metaphors, personifications, etc.
Keywords: Լեզուաբանութիւն; Քարոզչութիւն